Integrating Innovation: South Australian Entrepreneurship Systems and Strategies - Göran Roos; Allan O'Connor (University of Adelaide Press, 2015)
South Australia is a small economy that faces a fundamental need to re-shape its approach to innovation. The manufacturing sector, as the backbone of the state's economy, has and will continue to change in its nature and form. This necessitates a re-think about how innovation happens and how the respective actors within an economy interact and engage with each other. In effect, innovation relies on intersections between people, knowledge, information sharing, ideas, financial and other resources. Innovation happens through regional social and economic system dynamics; innovation relies on a system view of entrepreneurship. Entrepreneurship can be taken as a study of the entrepreneur and new business creation. However, this conception of entrepreneurship misses the critical link to economic outcomes; the ebb and flow of social and economic fortunes that are underpinned by the actions, reactions and engagement of individuals in a specific social and economic system that brings about innovation and change. In this book the authors are exploring how the linkages within the system can be conceptualised and made transparent.
Keywords: 330; integrating innovation; systems; south australia; economy; manufacturing sector; entrepreneurship; new business creation; business; intellectual capital; innovation; innovative; polity path dependency; allan o'connor; goran roos; jane andrew; kym teh; innovating systems symbiosis; gavin artz; huanmei li; clusters; yalumba; operationalising; operationalizing; hotwiring; fiona kerr; nonprofit social enterprises; eva balan-vnuk; peter balan; vernon ireland; graciela corral dezubielqui; pi-shen seet; paul shum; innovation readiness; jiwat ram; erp systems